2004
DOI: 10.1254/jphs.94.261
|View full text |Cite
|
Sign up to set email alerts
|

Possible Involvement of p38 in Mechanisms Underlying Acceleration of Proliferation by 15-Deoxy-Δ12,14-prostaglandin J2 and the Precursors in Leukemia Cell Line THP-1

Abstract: Abstract. 15-Deoxy-D12,14 -prostaglandin J 2 (15dPGJ 2 ), which is a ligand for peroxisome proliferator-activated receptor g (PPARg), induced apoptosis of several human tumors including gastric, lung, colon, prostate, and breast. However, the role of PPARg signals in other types of cancer cells (e.g., leukemia) except solid cancer cells is still unclear. The aim of this study is to evaluate the ability of 15dPGJ 2 to modify the proliferation of the human leukemia cell line THP-1. 15dPGJ 2 at 5 mM stimulated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 39 publications
2
9
0
Order By: Relevance
“…In breast cancer, p21 and p27 have received considerable attention as clinical indicators and potential targets in therapeutic development (28)(29)(30). In agreement with the findings we present here, previous work in leukemia showed that impaired MKK3 signals enhanced prostaglandin PGJ2-induced proliferation, and described impaired p21 and p27 expression in treated THP-1 cells (35). In addition, a natural fungal product (FTY720) induced MKK3 activity and p21 expression in prostate cancer cells, leading to cell-cycle arrest (36), whereas studies in muscle cell differentiation have shown that dominant negative MKK3 inhibits p21 and p27 expression (37).…”
Section: Discussionsupporting
confidence: 91%
“…In breast cancer, p21 and p27 have received considerable attention as clinical indicators and potential targets in therapeutic development (28)(29)(30). In agreement with the findings we present here, previous work in leukemia showed that impaired MKK3 signals enhanced prostaglandin PGJ2-induced proliferation, and described impaired p21 and p27 expression in treated THP-1 cells (35). In addition, a natural fungal product (FTY720) induced MKK3 activity and p21 expression in prostate cancer cells, leading to cell-cycle arrest (36), whereas studies in muscle cell differentiation have shown that dominant negative MKK3 inhibits p21 and p27 expression (37).…”
Section: Discussionsupporting
confidence: 91%
“…However, recent studies revealed that both PGD 2 and 15d-PGJ(2) appear to possess not only anti-inflammatory activities but also a proinflammatory potential depending on its concentration and the activation state of the target cell. For instance, PGD 2 or 15dPGJ2 stimulated the proliferation in the leukocyte cell line THP-1 at lower concentrations, whereas they inhibited the proliferation through the induction of apoptosis at high concentrations (3). In addition to the immune system, 15dPGJ 2 is suggested to play proinflammatory roles by inducing apoptosis of several human epithelial cell lines, including gastric, lung, colon, prostate, and breast.…”
Section: Discussionmentioning
confidence: 99%
“…The generation of 15d-PGJ 2 has been reported to increase under inflammatory conditions associated with COX-2 induction (Gilroy et al, 1999 2008). Thus, 15d-PGJ 2 potentiates mouse skin tumor formation (Millan et al, 2006), accelerates the proliferation of leukemia cells (Azuma et al, 2004) and colorectal cancer cells (Chinery et al, 1999) and has a capability to induce angiogenesis (Chinery et al, 1999;Azuma et al, 2004). Correlation between COX-2 expression and p53 accumulation has been suggested in human cancer tissues (Biramijamal et al, 2001;Leung et al, 2001;Shigemasa et al, 2003).…”
Section: Discussionmentioning
confidence: 99%